UDSIGELSE OG KULTURMØDER: Om sammenhængen mellem postkolonial litteratur og ansættelse af nydanskere - Bojsen, Heidi (Tidsskriftet Antropologi, 2007)
This article sets out to discuss how we may work with the notion of ‘cultural encounters’. Two examples are presented and discussed: One is drawn from the novel Monnè, outrages et défis (1990) by the prize-winning Ivorian author Ahmadou Kourouma. The other example refers to a job interview of an ethnic minority Dane in Denmark, published in a review by a Danish municipal administration (Århus Kommune) in 2003. The article brings a number of critical literary theories into dialogue in order to discuss two major points. First, the article shows how the chosen theoretical notions can help us to describe what happens in situations of communication where different, and possibly incommensurable, agents and contexts meet and interact in settings that are marked by conceptions of cultural differences. The theories used are Michel Foucault’s discursive formations, Emile Benveniste’s concept of enunciation, Mikhail Bakhtin’s reflexions of contrapuntal narratives, and Homi Bhabha’s theorisation of the anteriority of the sign as it occurs in a disjunctive temporality. Secondly, the article introduces a new interpretative method of how literary texts and critical literary theory may be used within anthropological studies. Instead of focusing on the notion of ‘identities’ and the ensuing conflicts between difference and sameness, this approach focuses on cultural articulations as dynamic communicative processes. In so doing, it situates itself within literary and anthropological theories of representation. Making a close reading of the chosen texts, the article shows that cultural encounters are never merely a question of ‘culture’. Cultural encounters become communicative scenarios where ideas, motives, intentions, and emotions are expressed, interpreted, and received by differently reacting agents.